Kinetika notranje oksidacije v hitro strjenih zlitinah Cu-Zr - Anžel, Ivan (Kovine zlitine tehnologije, 1997)
The combination of rapid solidification and internal oxidation represents the promising procedre for producing oxide-dispersion strengthened copper alloys with a fine dispersion of high temprature stable oxide particles of alloying elements with a low solid solubility in copper. Because of the reduced microsegregation and fine dispersion of the second phase particles obtained in rapid solidification, the internal oxidation of the rapidly solidified ribbons can be treated as internal oxidation of a two-phase alloy. The mechanism and kinetics of the oxidation are in such conditions specific and depend also on the process in the microstructure before oxidation. In this paper the results of studying the internal oxidation kinetics in rapidly solidified Cu-Zr alloys are presented. The models of the internal oxidation mechanism at different temperatures of oxidation were proposed and the depth of the internal oxidation front as a function of time were measured and compared with the theoretical values.
Keywords: Metallurgical and Materials Engineering; metalurgija; zlitine; kemijska kinetika; baker; cirkonij; zirconium; oksidacija; strjevanje; utrjevanje